A Systematic Review of Factor XI/XIa Inhibitors Versus Direct Oral Anticoagulants in Patients with Atrial Fibrillation - Zhengbiao Xue MS; Song Liao MS; Haiye Fan MS; Yu Shen MS; Zhi Nie MS (Clinical and Applied Thrombosis/Hemostasis)
Background Atrial fibrillation (AF) is a leading cause of stroke, necessitating effective anticoagulation. While direct oral anticoagulants (DOACs) have improved stroke prevention, bleeding risks remain a concern. Factor XI/XIa inhibitors, targeting the intrinsic coagulation pathway, offer potential for reduced bleeding, although questions remain regarding their efficacy. This systematic review evaluates the efficacy and safety of Factor XI/XIa inhibitors compared to DOACs in AF patients. Methods We conducted a systematic review of randomized controlled trials (RCTs) comparing Factor XI/XIa inhibitors with DOACs in AF patients, identified through PubMed and Embase up to January 2025. Data were synthesized narratively due to heterogeneity in study designs and outcomes. Results Three RCTs (AZALEA-TIMI 71, OCEANIC-AF, PACIFIC-AF) involving 16 852 patients were included. Factor XI/XIa inhibitors (abelacimab and asundexian) demonstrated significant reductions in bleeding compared to DOACs. In AZALEA-TIMI 71, abelacimab reduced major or clinically relevant non-major bleeding by 62%-69% versus rivaroxaban. In PACIFIC-AF, asundexian reduced bleeding by 50%-84% compared to apixaban. However, OCEANIC-AF showed asundexian was inferior in stroke prevention, with a 3.8-fold higher risk of stroke or systemic embolism compared to apixaban, leading to early trial termination. Abelacimab showed a trend toward higher ischemic stroke rates abelacimab (150 mg: 1.21 vs 0.59 events/100 person-years; and 90 mg: 1.24 vs 0.59 events/100 person-years), though not statistically significant. Conclusion Factor XI/XIa inhibitors significantly reduce bleeding risk in AF patients compared to DOACs, but their thrombotic efficacy remains uncertain. While promising, further research is needed to optimize their use.